2017
DOI: 10.5334/dsj-2017-039
|View full text |Cite
|
Sign up to set email alerts
|

Persistence Statements: Describing Digital Stickiness

Abstract: In this paper we present a draft vocabulary for making "persistence statements." These are simple tools for pragmatically addressing the concern that anyone feels upon experiencing a broken web link. Scholars increasingly use scientific and cultural assets in digital form, but choosing which among many objects to cite for the long term can be difficult. There are few well-defined terms to describe the various kinds and qualities of persistence that object repositories and identifier resolvers do or don't provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…There has been some research in this area, but more is needed. For instance, Puente and Díaz [57] look at using mindmaps in wiki refactors; Greenberg et al, discuss the need for a "community-driven metadata vocabulary application" that would support collaborative definition negotiation and term selection [30]; and Kunze et al describe a system for supporting the evaluation of "digital stickiness" of a term or identifier -basically, a way of assessing the potential longevity of a resources [46]. These approaches are promising but further workflows and workbenches are needed that tie these processes and resources together, and thereby better support the articulation work of semantic refactoring.…”
Section: Implications For Other Cooperative Classification Workersmentioning
confidence: 99%
“…There has been some research in this area, but more is needed. For instance, Puente and Díaz [57] look at using mindmaps in wiki refactors; Greenberg et al, discuss the need for a "community-driven metadata vocabulary application" that would support collaborative definition negotiation and term selection [30]; and Kunze et al describe a system for supporting the evaluation of "digital stickiness" of a term or identifier -basically, a way of assessing the potential longevity of a resources [46]. These approaches are promising but further workflows and workbenches are needed that tie these processes and resources together, and thereby better support the articulation work of semantic refactoring.…”
Section: Implications For Other Cooperative Classification Workersmentioning
confidence: 99%
“…Research on metadata longevity Sugimoto et al, 2016) has resulted in a framework solution for preserving metadata. Additionally, Kunze et al (2016a;2016b) present complementary work developing a persistence vocabulary. These are significant initiatives that can help further formalize our understanding of preservation as a principle for smart metadata.…”
Section: Expert Reviewmentioning
confidence: 99%
“…Over time, unlike journal references in papers, which may have a collective stable 'marker' or persistent identifier (PID) like a digital object identifier (DOI), allowing them to be identified and traced even if the journal's uniform resource locator (URL) 1 changes, the URLs of web-based references might become dysfunctional (i.e., links may become broken), or the URL might disappear altogether if the website shuts down or ceases to exist, a phenomenon known as reference rot (Burnhill et al, 2015). Kunze et al (2017) suggested the establishment of a lexicon to describe PIDs that would allow a user, such as an academic, to evaluate the level of durability of an identifier, including of a provider, before deciding whether to cite it. Entities that issue PIDs can enhance the reliability of a PID by following several management principles (McMurry et al, 2017).…”
mentioning
confidence: 99%